2019
DOI: 10.1002/jcp.29219
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2–ARE signaling in cellular protection: Mechanism of action and the regulatory mechanisms

Abstract: Oxidative stress is the increase in cellular oxidant concentration in comparison to antioxidant titer. Toxic insults and many other diseased conditions are mediated through the formation of such condition. Once the redox equilibrium is disrupted, the cellular antioxidant system functions to bring back the cell to redox homeostasis state. The field players of the cytoprotective machinery are the xenobiotic‐metabolizing enzymes that are transcriptionally controlled by upstream regulatory pathways like the Nrf2–A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
170
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(202 citation statements)
references
References 90 publications
2
170
0
1
Order By: Relevance
“…In normal non-stressed conditions, the Nrf2 is connected to its cytoplasmatic inhibitor-Kelch-like ECH-associated protein-1 (Keap1). When oxidative stress increases, Nrf2 is released from Keap1, then translocated to the nucleus where it connects with antioxidant response element (ARE), inducing the expression of Nrf2-ARE dependent genes, including the genes coding antioxidative enzymes [70]. We observed that SOD and CAT activity was significantly increased in the lenses of diabetic rats.…”
Section: Discussionmentioning
confidence: 89%
“…In normal non-stressed conditions, the Nrf2 is connected to its cytoplasmatic inhibitor-Kelch-like ECH-associated protein-1 (Keap1). When oxidative stress increases, Nrf2 is released from Keap1, then translocated to the nucleus where it connects with antioxidant response element (ARE), inducing the expression of Nrf2-ARE dependent genes, including the genes coding antioxidative enzymes [70]. We observed that SOD and CAT activity was significantly increased in the lenses of diabetic rats.…”
Section: Discussionmentioning
confidence: 89%
“…One of the most intriguing features of many regulated transcription factors is their mechanism of activation [6]. For example, certain stress-regulated transcription factors are responsive to oxygen depletion (e.g., hypoxia-inducible factor 1α (HIF1α) [7], oxidative stress (e.g., nuclear factor erythroid 2-like factor 2 (NRF2)) [8] and growth factors (e.g., serum response factor (SRF)) [9]. This review focuses on activating transcription factor 6α (ATF6α), a transcription factor that was originally found to be activated by ER proteotoxic stress [10], i.e., protein-misfolding in the ER, but more recently has been found to be activated by a wider array of stresses [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nrf2 is a predominant regulator of cellular defense mechanism against oxidative stress because it can regulate the expression activity of various genes which are crucial in response to oxidative stress [10,11] . Recently, Nrf2 has been treated as a potent terminator for oxidative stress injury due to its ability in greatly reducing oxidative stress level in alveolar epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the way that Nrf2 suppresses the expression of NOX1 is still undiscovered. Given that the Nrf2-antioxidant response element signaling strongly facilitates to maintain the balance between oxidant system and antioxidant system under oxidative stress condition [11] and that the existence possibility of Nrf2 binding element in the promoter of NOX1, it is reasonable to assume that the predicted binding element plays a pivotal role in the interaction between Nrf2 and NOX1. To con rm this hypothesis, the sequence of Nrf2 binding element was deleted and a deletion mutant of NOX1 promoter were synthesized by overlap extension PCR, after that, two recombinant plasmids were constructed by inserting the sequence of full-length of NOX1 promoter and that of the deletion mutant to the pGL3 basic plasmid and transformed these plasmids into A549 cells under the induction of TNF-α.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation